1999
DOI: 10.2105/ajph.89.6.899
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health risk assessment and counseling in primary care: how involved are general practitioners and obstetrician-gynecologists?

Abstract: Sexually transmitted diseases (STDs) are important causes of pelvic inflammatory disease, infertility, ectopic pregnancy, and neonatal morbidity in North America.' Each (2) their counseling about STD prevention during specific consultations for adolescent contraception and treatment of an STD. MethodsData are presented from a 1995 anonymous mail survey conducted in the province of Quebec, Canada. Physicians' demographic and professional data were provided by the College des medecins du Quebec. To be include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 18 publications
3
21
1
4
Order By: Relevance
“…This reluctance to vaccinate young adolescents may be due to provider beliefs that young adolescents are not at imminent risk for HPV infection, or discomfort discussing sexuality issues with younger teens or their parents. Although the providers in our study reported a high level of comfort addressing issues of adolescent sexuality, their report is inconsistent with previous studies of family physicians 31,32 and in our study those who did report discomfort addressing sexuality issues reported lower intention to recommend HPV vaccination. The finding that providers are reluctant to vaccinate young adolescents is problematic in that prophylactic STI vaccination ideally should occur before sexual initiation and by ninth grade, approximately one third of U.S. adolescents have initiated sexual intercourse.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This reluctance to vaccinate young adolescents may be due to provider beliefs that young adolescents are not at imminent risk for HPV infection, or discomfort discussing sexuality issues with younger teens or their parents. Although the providers in our study reported a high level of comfort addressing issues of adolescent sexuality, their report is inconsistent with previous studies of family physicians 31,32 and in our study those who did report discomfort addressing sexuality issues reported lower intention to recommend HPV vaccination. The finding that providers are reluctant to vaccinate young adolescents is problematic in that prophylactic STI vaccination ideally should occur before sexual initiation and by ninth grade, approximately one third of U.S. adolescents have initiated sexual intercourse.…”
Section: Discussioncontrasting
confidence: 99%
“…Female physicians may be focused on cervical cancer as a women's health issue, and they may be more comfortable in addressing sexual health issues. 32 Physicians who focus on women's health issues or work with patients at high risk for HPV-related disease (e.g. patients who are immunocompromised) may have a better understanding of HPV infection and its sequelae, and thus may recognize the potential health benefits of an HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…C'est ainsi que les problématiques associées au VIH/sida (consommation de drogues illégales ou thèmes en relation avec la sexualité) retiennent nettement moins l'attention que la consommation de tabac et d'alcool ou l'activité physique lors de l'anamnèse d'un jeune adulte. Une telle tendance est aussi relevée ailleurs [14]. S'expliquant en partie par le fait qu'il est probablement plus aisé d'aborder ces thèmes que de parler de la sexualité ou de consommation de stupé-fiants, ce relatif désintérêt prive les médecins d'informations nécessaires pour délivrer des messages de prévention adaptés à la réalité de leurs patients.…”
Section: Discussionunclassified
“…They were more concerned about patient discomfort [38]. Good strategies for the care of mental illness and risk reduction cannot be without gender.…”
Section: Gendermentioning
confidence: 99%